THE EFFECT OF SOCIAL MEDIA USE ON STUDENTS FINANCIAL MANAGEMENT BEHAVIOR WITH SELF CONTROL AS A MODERATING VARIABLE - Dewi Kusuma Wardani; Anita Primastiwi; Rosina Helisastri (Jurnal Ilmu Manajemen Profitability, 2022)
This study aims to examine the effect of using social media on financial management behaviour with self-control as a moderating variable. This type of research is a quantitative research. Data collection in this study used primary data by distributing questionnaires to student of the ecocomics faculty of the University of Sarjanawiyata Tamansiswa Yogyakarta. The technique used in sampling is convenience sampling. Data collection is done by spreading the google form link through the whatsapp application to student. The number of questionnaires that were processed were 100 questionnaires. Data were analyzed using path analysis. The result showed that the use of social media had no effect on student financial management behaviour. Self control cannot strengthen the positive effect of using social media on student financial management behaviour